2018
DOI: 10.1007/s10853-018-2409-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of the synthesis and characterization of anion exchange membranes

Abstract: This review highlights advancements made in anion exchange membrane (AEM) head groups, polymer structures and membrane synthesis methods. Limitations of current analytical techniques for characterizing AEMs are also discussed. AEM research is primarily driven by the need to develop suitable AEMs for the high-pH and high-temperature environments in anion exchange membrane fuel cells and anion exchange membrane water electrolysis applications. AEM head groups can be broadly classified as nitrogen based (e.g. qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
194
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(211 citation statements)
references
References 123 publications
(248 reference statements)
1
194
0
1
Order By: Relevance
“…Quaternary ammonium (QA)-based anion exchange membranes (AEMs) have been studied extensively for fuel cell and electrolyser application due to their ease of functionalisation and high hydroxide ion conductivity. [1][2][3] Commonly employed cationic head groups based on QA are benzyl-trialkylammonium such as functionalised with trimethyl amine (TMA), QA with bridged bicyclic amines such as 1,4-diazabicyclo[2.2.2] octane (DABCO) and 1-azabicylo[2.2.2]octane (ABCO), and cycloaliphatic QA such as N-methylpiperidine (NMP). However, QA-functionalised AEMs have poor stability in high pH conditions due to base-induced degradation mechanisms, namely, Hofmann elimination, nucleophilic substitution, and ylide formation pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quaternary ammonium (QA)-based anion exchange membranes (AEMs) have been studied extensively for fuel cell and electrolyser application due to their ease of functionalisation and high hydroxide ion conductivity. [1][2][3] Commonly employed cationic head groups based on QA are benzyl-trialkylammonium such as functionalised with trimethyl amine (TMA), QA with bridged bicyclic amines such as 1,4-diazabicyclo[2.2.2] octane (DABCO) and 1-azabicylo[2.2.2]octane (ABCO), and cycloaliphatic QA such as N-methylpiperidine (NMP). However, QA-functionalised AEMs have poor stability in high pH conditions due to base-induced degradation mechanisms, namely, Hofmann elimination, nucleophilic substitution, and ylide formation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, QA-functionalised AEMs have poor stability in high pH conditions due to base-induced degradation mechanisms, namely, Hofmann elimination, nucleophilic substitution, and ylide formation pathway. [2][3][4][5] Richard Espiritu and John Lester Tan contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, many studies have demonstrated that hydroxide conductivity and other performance characteristics of the AEM membranes require further improvement. 26,33,34 Recently, many researchers have sought to enhance the physicochemical properties of the polymer electrolyte membranes by adding fillers such as ionic liquids and inorganic nanoparticles [35][36][37][38][39] (ZrO 2 , 40 SiO 2 , 39 and CNTs [41][42][43][44] ). Wen et al 45 found that addition of ionic liquids in polymer films did enhance the OH − conductivity and performance in SC.…”
Section: Introductionmentioning
confidence: 99%
“…Anion exchange membranes (AEMs), one of the crucial components of ADMFCs, participate in anion transport and fuel/oxidant separation. Now, series of polymers like polyethers, polyketone, polysulfones, polyaromatics with aryl ether‐free backbones, etc have been developed as AEMs, among which polybenzimidazoles (PBIs) have been regarded as one of the desirable alkaline polymer electrode membrane matrixes because PBIs perform high mechanical properties and good alkali resistance even at an elevated temperature . Moreover, the nitrogen including ‐NH‐ and ‐N= in the polymer scaffold can absorb and interact with the hydroxide ions, which are beneficial for the ions conduction .…”
Section: Introductionmentioning
confidence: 99%
“…Now, series of polymers like polyethers, 2-6 polyketone, 7,8 polysulfones, [9][10][11][12][13][14] polyaromatics with aryl ether-free backbones, 15 etc have been developed as AEMs, among which polybenzimidazoles (PBIs) have been regarded as one of the desirable alkaline polymer electrode membrane matrixes because PBIs perform high mechanical properties and good alkali resistance even at an elevated temperature. [16][17][18][19][20][21][22][23][24][25][26] Moreover, the nitrogen including -NH-and -N= in the polymer scaffold can absorb and interact with the hydroxide ions, which are beneficial for the ions conduction. 17,27 However, compared to acid-doped PBI membranes, the alkali-doped PBI membranes displayed lower ionic conductivity, because the diffusion coefficient of hydroxide ions is only one quarter of that of protons, suggesting that a high alkali-doped PBI membranes are been expected.…”
Section: Introductionmentioning
confidence: 99%